Projecting the World : Representing the "Foreign" in Classical Hollywood - Meeuf, Russell, 1981-; Cooper, Anna (Book collections on Project MUSE., 2017)
"The classical Hollywood films that were released between the 1930s and 1960s were some of the most famous products of global trade, crisscrossing borders and rising to international dominance. In analyzing a series of Hollywood films that illustrate moments of nuanced transnational engagement with the "foreign," Projecting the World: Representing the "Foreign" in Classical Hollywood enriches our understanding of mid-twentieth-century Hollywood cinema as a locus of imaginative geographies that explore the United States' relationship with the world. While previous scholarship has asserted the imperialism and racism at the core of classical Hollywood cinema, Anna Cooper and Russell Meeuf's collection delves into the intricacies--and sometimes disruptions--of this assumption, seeing Hollywood films as multivalent and contradictory cultural narratives about identity and politics in an increasingly interconnected world. Projecting the World illustrates how Hollywood films negotiate shifting historical contexts of internationalization through complex narratives about transnational exchange--a topic that has thus far been neglected in scholarship on classical Hollywood. The essays analyze the "foreign" with topics such as the 1930s island horror film, the 1950s Mexico-set bullfighting film, Hollywood's projection of "exoticism" on Argentina, and John Wayne's film sets in Africa. Against the backdrop of expanding consumer capitalism and the growth of U.S. global power, Hollywood films such as Tarzan and Anatahan, as well as musicals about Paris, offered resonant images and stories that dramatized America's international relationships in complicated ways. A fascinating exploration of an oft-overlooked aspect of classical Hollywood films, Projecting the World offers a series of striking new analyses that will entice cinema lovers, film historians, and those interested in the history of American neocolonialism."--Publisher's description